IMPLEMENTASI PASAL 70 PERATURAN KOMISI PEMILIHAN UMUM NOMOR 15 TAHUN 2023 TENTANG KAMPANYE PEMILIHAN UMUM DALAM PERSPEKTIF SIYASAH TANFIDZIYAH - Jeriyansyah; Syukur, Iskandar; Burhanuddin, Ahmad (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2026)
General Elections serve as a means of implementing popular sovereignty within a democratic system. However, during the campaign period, violations frequently occur, particularly concerning the installation of Campaign Props (Alat Peraga Kampanye/APK). Article 70 of the General Election Commission Regulation (PKPU) Number 15 of 2023 prohibits the installation and posting of campaign props in certain locations, thereby requiring the role of a supervisory institution to prevent and address such violations. This study aims to analyze the implementation of this provision and examine it from the perspective of Siyāsah Tanfiźiyah. This research is a field study employing a descriptive qualitative approach. Primary data were obtained through interviews with informants, while secondary data were derived from literature, documentation, and archives of the North Lampung Regency Bawaslu. Data collection techniques included observation, interviews, and documentation, which were analyzed through data verification, coding, and systematization. The findings indicate that Bawaslu of North Lampung has carried out preventive measures through socialization to election participants and has taken enforcement actions against campaign prop violations. From the perspective of Siyāsah Tanfiźiyah, these efforts align with the principles of public welfare (maslahah), trust (amanah), and the responsibility of ulil amri in upholding regulations for the benefit of society.